Late Outcome after Surgery for Type-A Aortic Dissection - Mikko Jormalainen; Peter Raivio; Fausto Biancari; Caius Mustonen; Hannu-Pekka Honkanen; Maarit Venermo; Antti Vento; Tatu Juvonen (MDPI, 2022)
The aim of this study was to evaluate all-cause mortality and aortic reoperations after surgery for Stanford type A aortic dissection (TAAD). We evaluated the late outcome of patients who underwent surgery for acute TAAD from January 2005 to December 2017 at the Helsinki University Hospital, Finland. We studied 309 patients (DeBakey type I TAAD: 89.3%) who underwent repair of TAAD. Aortic root repair was performed in 94 patients (30.4%), hemiarch repair in 264 patients (85.4%) and partial/total aortic arch repair in 32 patients (10.4%). Hospital mortality was 13.6%. At 10 years, all-cause mortality was 34.9%, and the cumulative incidence of aortic reoperation or late aortic-related death was 15.6%, of any aortic reoperation 14.6%, reoperation on the aortic root 6.6%, on the aortic arch, descending thoracic and/or abdominal aorta 8.7%, on the descending thoracic and/or abdominal aorta 6.4%, and on the abdominal aorta 3.8%. At 10 years, cumulative incidence of reoperation on the distal aorta was higher in patients with a diameter of the descending thoracic aorta >= 35 mm at primary surgery (cumulative incidence in the overall series: 13.2% vs. 4.0%, SHR 3.993, 95%CI 1.316-12.120; DeBakey type I aortic dissection: 13.6% vs. 4.5%, SHR 3.610, 95%CI 1.193-10.913; patients with dissected descending thoracic aorta: 15.8% vs. 5.9%, SHR 3.211, 95%CI 1.067-9.664). In conclusion, surgical repair of TAAD limited to the aortic segments involved by the intimal tear was associated with favorable survival and a low rate of aortic reoperations. However, patients with enlarged descending thoracic aorta at primary surgery had higher risk of late reoperation. Half of the distal aortic reinterventions were performed on the abdominal aorta.